The marketing orientation of owner – managers / Sue Birley and Bashir EL-Rayyes (Faculty of Business and Management ; UiTM Press, 1996)
Marketing is an important factor in small firms survival and growth. However, the majority of the literature available is based upon opinion and lacks empirical investigation, often simply me asuring the small firm on a Dichotomisedscale of marketing or no-marketing. This research investigates the degree of marketing orientation amongst a sample of owner-managed firms, and reports on different typologies of owner-managers based on their attitude towards marketing. The study draws upon 128 small manufacturing firms in Bedfordshire, U.K. Firms in the sample range in size from 5 to 105 employees, from £50,000 to over £5 million sales, and from less than £50,000 to over £1 million profit.